2001
DOI: 10.1002/jcp.1063
|View full text |Cite
|
Sign up to set email alerts
|

P2Y2 nucleotide receptor signaling in human monocytic cells: Activation, desensitization and coupling to mitogen‐activated protein kinases

Abstract: Activation of P2Y(2) receptors by extracellular nucleotides has been shown to induce phenotypic differentiation of human promonocytic U937 cells that is associated with the inflammatory response. The P2Y(2) receptor agonist, UTP, induced the phosphorylation of the MAP kinases MEK1/2 and ERK1/2 in a sequential manner, since ERK1/2 phosphorylation was abolished by the MEK1/2 inhibitor PD 098059. Other results indicated that P2Y(2) receptors can couple to MAP kinases via phosphatidylinositol 3-kinase (PI3K) and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
45
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 58 publications
(51 citation statements)
references
References 53 publications
6
45
0
Order By: Relevance
“…EC50 values for Ca 2+ mobilization determined with the HA-tagged P2Y 2 receptor transfected cells (0.32 μM; Table 1) were similar to those obtained by us (20) for endogenous P2Y 2 receptors in human monocytic U-937 cells (0.44 μM). A 15 min treatment with 100 μM UTP produced rapid desensitization showing an IC50 value of 6.3 μM (Table 1).…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…EC50 values for Ca 2+ mobilization determined with the HA-tagged P2Y 2 receptor transfected cells (0.32 μM; Table 1) were similar to those obtained by us (20) for endogenous P2Y 2 receptors in human monocytic U-937 cells (0.44 μM). A 15 min treatment with 100 μM UTP produced rapid desensitization showing an IC50 value of 6.3 μM (Table 1).…”
Section: Discussionsupporting
confidence: 83%
“…Previous reports have suggested that receptor phosphorylation plays a role in the modulation of P2Y 2 receptor desensitization and recovery (9,20). Consistent with this idea, we observed that recovery of P2Y 2 receptor signaling after agonist-induced desensitization was inhibited in 50% upon treatment with 1 μM of the protein phosphatase inhibitor okadaic acid (Figure 3).…”
Section: Agonist-mediated P2y2 Receptor Desensitization Involves Phossupporting
confidence: 90%
See 1 more Smart Citation
“…Desensitization is a common process that regulates the functional responsiveness of both P2YRs (Otero et al, 2000;Santiago-Pérez et al, 2001) and CysLTs (Winkler et al, 1988). Heterologous regulation between P2YRs and CysLTs has been demonstrated in human monocyte/macrophage-like cells, in which the activation of P2YRs with ATP or UDP induced the desensitization of the CysLT 1 .…”
Section: Introductionmentioning
confidence: 99%
“…A well-defined effect of nucleotides on platelet activation and vascular smooth muscle migration and growth has suggested participation of P2Y receptors in the response to injury. More recently, these receptors have been noted to affect cellular constituents of the innate immune system altering functional characteristics of monocytes, eosinophils, and dendritic cells and to play a critical role in terminating the inflammatory response in vivo (Mutini et al 1999;Ferrari et al 2000;Idzko et al 2001;Santiago-Perez et al 2001;Warny et al 2001;Wilkin et al 2001). The P2Y receptor specificity originally thought to be restricted to purine (adenine) nucleotides has been extended to pyrimidine nucleotides (uridine) and more recently to a receptor with specificity for UDP, but only when conjugated to glucose or related sugars (Chambers et al 2000).…”
mentioning
confidence: 99%